Analysis of Medical Audit Management on Electronic Medical Records at Ngudi Waluyo Wlingi Regional General Hospital - Nugraheni, Shevia Dwi; Rusdi, Achmad Jaelani; Ikawati, Fita Rusdian (PROMOTOR, 2025)
Medical audits aim to improve the quality of health services and ensure compliance with standard operating procedures (SOPs). The application of electronic medical records (RME) at Ngudi Waluyo Wlingi Hospital to improve documentation efficiency and reduce recording errors. This study aims to analyze the management of medical audits on electronic medical records at Ngudi Waluyo Wlingi Hospital, focusing on audit procedures, human resource factors, and facilities and infrastructure that support the implementation of medical audits. The method used in this study is qualitative with a descriptive approach, which is carried out through in-depth interviews and observations. The informants in this study consisted of the doctor conducting the audit, the head of the IT unit, and the head of the medical record. The results of the study show that the medical audit procedure has been carried out in accordance with applicable standards, but there are still obstacles in coordination between teams and lack of training for auditors and medical personnel. The human resource factor is the main challenge, where the limited understanding of medical personnel on audit procedures and the use of the RME system has an impact on the effectiveness of audits. To increase the effectiveness of medical audits, it is necessary to increase training for medical personnel and auditors, strengthen coordination between audit teams and medical staff, and optimize the RME system to make it more integrated and accessible. The implementation of audit recommendations in hospital policies must be improved to support continuous service improvement.